Platform convergence in Indonesia: Challenges and opportunities for media freedom. (May 2015) - Tapsell, Ross
This article examines media freedom in Indonesia, an age where the media landscape is being remade by convergence. Media scholars are debating the implications of this trend for media freedom, with some believing it is opening new possibilities for a greater range of voices to be heard and others identifying new threats it poses. The Indonesian case, where media freedom is viewed as threatened, shows how technological convergence has led to commercial convergence. This article explores how convergence is both contributing to and undermining media freedom in Indonesia. It will do so through an in-depth analysis of the current trends in the Indonesian media industry.